Telehealth in Remote Areas: A New Artificial Intelligence-Based Model - Bagus Setya Rintyarna; Sasmiyanto; Odilia D. Insantuan; Ida Widiawati; Reza Yuridian Purwoko (International Journal of Science and Society, 2023)
The existence of technology has led to many developments in various fields, including health. Telehealth through the use of artificial intelligence can help increase access to health, especially in remote areas. This study aims to describe the potential and challenges of implementing an artificial intelligence (AI) based Telehealth model in increasing access to health in remote areas. Using descriptive qualitative research methods with thematic data analysis, this research analyzes data obtained from literature studies and previous research related to Telehealth AI. The results reveal that Telehealth AI has the potential to reduce inequalities in access to health, improve health outcomes, and save healthcare systems costs. However, challenges such as adequate regulation, data security, limited technological infrastructure, and digital literacy need to be overcome to maximize benefits. This research provides important insights to support the development of effective and inclusive Telehealth AI in remote areas.